COVID-19 risk in youth club sports: A nationwide sample representing over 200,000 athletes - Biese, K. M.; McGuine, T. A.; Haraldsdottir, K.; Goodavish, L.; Watson, A. M. (Journal of Athletic Training, 2021)
Context: The COVID-19 pandemic has affected almost every aspect of life including youth sports. Little data exists on COVID-19 incidences and risk mitigation strategies in youth club sports.